Sargassum filipendula, a Source of Bioactive Compounds with Antioxidant and Matrix Metalloproteinases Inhibition Activities In Vitro with Potential Dermocosmetic Application (2023)
ABSTRACT: The antioxidant and the potential inhibitory capacity of matrix metalloproteinases of the phlorotannin-type polyphenolic and fucoidan-type polysaccharides extracts obtained from the macroalga S. filipendula were evaluated. Through chromatographic and spectroscopic techniques, the corresponding chemical structure of compounds present in the extracts was determined. Antioxidant capacity was evaluated using the methyl linoleate model for the inhibition of lipid peroxidation, and the free radical scavenging capacity was assessed using DPPH, ABTS, •OH, O2 •− methods. The matrix metalloproteinase inhibition potential was measured by collagenase and elastase inhibition tests, using epigallocatechin gallate as a positive control. The extracts exhibited a high scavenging capacity of radical species evaluated and inhibition of diene conjugate formation and thiobarbituric acid reactive substances. The results showed that the crude extracts presented dose-dependent collagenase and elastase inhibition, with IC50 values between 0.04 and 1.61 mg/mL. The structure of the residues of the polysaccharide was identified mainly as (1→3)-sulfated (1→3) α-L-fucopyranose at carbon 4 and residues of β-D-glucopyranose, α-D-Mannopyranose, and β-D-Galactopyranose, while in the polyphenol extract the presence of phloroglucinol was identified and the presence of eckol, bifuhalol, and trifuhalol was suggested. Our results allow us to infer that S. filipendula is a potential source of bioactive ingredients with antioxidant and anti-aging activity.